Research of the process of the ink dry faster membrane water-in-oil emulsion, using catalytic complex [Co(Acac)]+ - Huỳnh, Lê Văn (Vietnam Journal of Chemistry, 2014)
Fast growing digital printers are widely used in all areas, by the superiority of them are: To meet the on time, high yield, quality guarantee and low cost. Ink for digital quick printers ink is water-in-oil emulsion, the need to have time to dry the ink film must fast during the printing process, so as not to affect the quality of the next printed sheet, to increase in output, requires ink film to dry quickly. To solve problems using complex catalyst. This paper is the application of research results catalyzed complex created by Co2+ with Axetylaxeton (Acac), the membrane during fast drying water-in-oil emulsion ink, used for digital quick printers. Putting catalytic complex [Co(Acac)]+ in water-in-oil emulsion ink, reduced drying time of the ink film from 223s to 65s, which was 4 times increase in output. Research results is the scientific basis for the application of complex catalytic applications in practical production process.